Pemanfaatan Ampas Tebu sebagai Adsorben untuk Penyisihan COD pada Limbah Cair Laboratorium - Tika Kumala Sari; Noven Pramitasari; Yeny Dhokhikah; Farid Nauval Nugraha; Nanda Diva Adea Fara (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Laboratory wastewater at the Environmental Engineering Study Program of Jember University (UNEJ) is wastewater generated from various practical activities and research involving the use of inorganic and organic chemicals. UNEJ Environmental Engineering laboratory wastewater is used as a means of supporting lectures and research for students and lecturers. The UNEJ Environmental Engineering Laboratory has never conducted tests on the characteristics of the wastewater produced. This study aims to examine the effectiveness of sugarcane bagasse in adsorbing COD levels in laboratory wastewater at various adsorbent heights and activator variations. The initial COD content of the laboratory wastewater was 665 mg/L. The variations in adsorbent height in the adsorption column reactor were 2 cm, 3 cm, 4 cm, and 5 cm, while the variations in sugarcane bagasse adsorbent activators were HCl, H3PO4, KOH, and Na2CO3. Based on the results of the study, the best COD removal efficiency was achieved with a column height variation of 5 cm and a KOH activator variation of 92.05%. The COD content in the initial laboratory wastewater of 665 mg/L after undergoing the adsorption process using bagasse waste adsorbent became 52.9 mg/L.